O yoga como prática para a autotransformação aplicada aos militares do BOPE que atuam em João Pessoa- PB - Costa, Samara Donato Tenório (2017)
Our dissertation had as general objective to analyze how the practice of Yoga can contribute to the self-transformation of the BOPE military of Paraíba. We used as a methodology the bibliographical research and field research, given the theoretical and practical nature that the research demands, serving as input for the analysis of the results of the techniques composed in Hatha Yoga, aiming to establish consistent information following a support to the observational study and practical. In order to have a general understanding of the practice of Yoga techniques we approach historical aspects of Yoga, Yoga Sutras of Patanjali, based on Hatha Yoga, the construction of the military body. With this we propose a Yoga practice that was applied to the BOPE's military who work in João Pessoa, PB and who have never practiced this science. We have resulted in transformations that we consider to be relevant given the limited time available for the practices. Our study showed that it is possible to self-transform from the minimum of the techniques of Yoga, for example, 3 minutes of meditation, 2 postures, a pranayama is capable of producing selftransformation in the BOPE police.